SIZE FRACTIONATION OF ZOOPLANKTON BIOMASS AND SPECIES COMPOSITION IN THE LAGOON OF PULAU PARI, SERIBU ISLANDS - Reny Puspasari (Widyariset, 2013)
Zooplankton is the main prey of fish larvae. The match between fish larvae and its prey depends on the size and the composition of zooplankton. The study aims to investigate the biomass and species composition of zooplankton and their relationship to the environmental conditions in Pulau Pari Lagoon. Research was conducted from June to November 2010. Results showed that 63,9% of zooplankton biomass consisted of microzooplankton, dominated by the class of Crustacea with subclass of Copepoda, and 36,1% of zooplankton biomass consisted of mesozooplankton, dominated by the class of Crustaceasu with subclass of Malacostraca. The biomass peak occurred at the end of July indicating the highest food availability and this could support fish larve survival.